Evaluation of functional rehabilitation physiotherapy protocol in the postoperative patients with anterior cruciate ligament reconstruction through clinical prognosis: An observational prospective study - Do Carmo Almeida, Tabata Cristina; De Alcantara Sousa, Luiz Vinicius; De Melo Lucena, Diego Monteiro; Dos Santos Figueiredo, Francisco Winter; Valenti, Vitor Engrácia [UNESP]; Da Silva Paiva, Laércio; De Abreu, Luiz Carlos; Adami, Fernando (Springer Nature, 2016)
Background: The aim of the study was to evaluate the evolution of patients subject to physical treatment based on guidelines of functional rehabilitation after surgery anterior cruciate ligament reconstruction. Methods: This is a prospective study of 177 patients with anterior cruciate ligament injury, who underwent surgery and physical therapy guideline conducted in an orthopedic clinic in São Paulo, southeastern Brazil. The clinical evolution of patients was made according to Lysholm and IKDC questionnaire on the 1st day after surgery with 30, 90 and 180 days of treatment. Results: There was statistically significant increase in the gross values of Lysholm and IKDC questionnaires during the treatment (p < 0.001), which indicates progressive gain of function. According to the scores obtained from the IKDC, it can be observed that in stage 1 the average progress was 53.5 %, falling to 50 % in stage 2, and 26.1 % in stage 3. As to Lysholm score, it started with 87.7 %, falling to 62.6 % in the second stage and 7 % in the third stage, both statistically significant (p < 0.001). The rehabilitation-oriented functional objectives priority is to quickly get the exercises to gain breadth, strength and proprioception, optimizing and improving the integration of the athlete back to sport. Conclusion: Synthesizing the gradual gain of function and according to clinical outcomes assessed by IKDC and Lysholm, the functional guideline presented may be considered an alternative for rehabilitation of patients in postoperative anterior cruciate ligament.
Keywords: Anterior cruciate ligament; Ligaments; Rehabilitation